Tragedy girls [videorecording (DVD)] - Howard, Russ, III (Gunpowder & Sky, 2018)
Best friends Sadie and McKayla are on a mission to boost their social media fandom as amateur crime reporters hot on the trail of a deranged local serial killer. After they manage to capture the killer and secretly hold him hostage, they realize the best way to get scoops on future victims would be to, you know, murder people themselves. As the @TragedyGirls become an overnight sensation and panic grips their small town, can their friendship survive the strain of national stardom? Will they get caught? Will their accounts get verified?